Multi-Platform Digital Marketing Strategy and Performance Metrics of Micro Creative Enterprises: A Case Study of Fairy Charm Beaded Accessories in Malang, Indonesia - Evi Suwarni; Wening Patmi Rahayu; Agus Hermawan (JURNAL RISET MANAJEMEN (JURMA), 2026)
The advancement of digital technology has created significant opportunities for micro enterprises to expand their market reach through various digital platforms. This study aims to analyze the digital marketing strategy and marketing performance measurement of Fairy Charm, a micro-scale beaded accessories business based in Malang, Indonesia. An exploratory case study method was employed, with data collected through observation, documentation, and digital metrics analysis. The findings reveal that Fairy Charm simultaneously implements a multi-platform digital marketing strategy across Instagram, TikTok, Shopee, WhatsApp Business, and Google My Business, guided by a 4P marketing mix approach. Performance metrics indicate 194 profile visits, 418 total social media impressions, 20 business interactions, and 40 products sold with an average order value of IDR 250,000. Although brand awareness remains limited, consistent visual content strategy and multi-platform management proved effective in establishing an online presence for a newly established business. This study provides practical insights for creative MSMEs in designing and measuring digital marketing strategies during the early stages of business development.